Persoalan Pengembangan Institusi Pemberdayaan Masyarakat - - Soetomo (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2006)
Transformation from production oriented development to people centered development requires a deeply rooted local institutions. The critical challenge to deal is how to manage the process of institutionalization